Lignans-rich extract of Schisandra chinensis prevent alcohol-associated liver disease by regulating the gut microbiota and tryptophan metabolism - Yan-Yu Chi; Jun-Yan Xiang; Hui-Min Li; Hao-Yu Shi; Ke Ning; Hongyu Xiang; Qiuhong Xie (Current Research in Food Science)
Alcohol-associated liver disease (ALD) has emerged as a global public health concern, and gut microbiota plays a decisive role in its pathogenesis. Schisandra chinensis, a functional edible berry, exhibits hepatoprotective properties. However, the preventive effects of its main active component lignans against ALD, as well as their connections with gut microbiota and intestinal metabolites remain unclear. This study employed a mouse model of ALD induced by chronic-binge ethanol feeding to evaluate the hepatoprotective effects of lignans-rich extract of S. chinensis (SCL) interventions at different doses. 16S rDNA sequencing and metabolomic analysis were used to investigate microbial and metabolite profiles in intestinal contents. The hepatoprotective activity of key metabolite responding to SCL was further verified by in vivo and in vitro experiments. The results demonstrated that SCL effectively restored intestinal barrier function and alleviated alcohol-induced hepatic injury. SCL modulated intestinal tryptophan (Trp) metabolism and restored indole-3-acetic acid (IAA) levels. Concurrently, SCL reshaped the gut microbiota composition, enriched L. reuteri. Further in vivo and in vitro investigations demonstrated that SCL-mediated enrichment of L. reuteri contributed to intestinal IAA restoration which reactivated the ethanol-suppressed AHR pathway, enhanced intestinal barrier integrity, reduced lipopolysaccharide translocation into circulation and ultimately attenuates liver injury. Collectively, SCL prevent ALD by regulating intestinal microbiota and Trp metabolism. This study provides a scientific foundation for the development of S. chinensis as a functional food for ALD prevention.